Multisensory modulation of experimentally evoked perceptual distortion of the face. (18th November 2017) - Dagsdóttir, L. K.; Bellan, V.; Skyt, I.; Vase, L.; Baad‐Hansen, L.; Castrillon, E.; Svensson, P.
Summary: Background: Chronic oro‐facial pain patients often perceive the painful face area as "swollen" without clinical signs, that is a perceptual distortion (PD). Local anaesthetic (LA) injections in healthy participants are also associated with PD. Objective: The aim was to explore whether PD evoked by LA into the infraorbital region could be modulated by adding mechanical stimulation (MS) to the affected area. Methods: Mechanical stimulation was given with a brush and a 128‐mN von Frey filament. Firstly, sixty healthy participants were randomly divided into three groups: (i) LA control, (ii) LA with MS, (iii) isotonic solution (ISO) with MS as an additional control condition. To further examine the role of a multisensory modulation, an additional experiment was conducted. Twenty participants received LA with MS (filament) in addition to visual feedback of their distorted face. The results of the two experiments are presented together. Results: All three LA groups experienced PD; per contra, PD was not reported in the ISO group. MS alone did not change the magnitude of PD: brush ( P  = .089), filament ( P  = .203). However, when the filament stimulation was combined with additional visual information of a distorted face, there was observable decrease in PD ( P  = .002). Conclusion: The findings indicate the importance of multisensory integration for PD and represent a significant step forward in the understanding of the factors that may influence this common condition. Future studies are encouraged to investigate further the cortical processing for possible implications for PD in pain management.